THE INFLUENCE OF MARKETING MIX AND SOCIAL FACTORS ON THE DECISION TO PURCHASE ROTIBOY IN THE CITY OF SURABAYA WITH THE PURCHASE EXPERIENCE MEDIATION VARIABLE - Reonaldo Putra Agung; Aldo Lovely Arief Suyoso; Dian Ekowati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Surabaya, as one of the metropolitan cities in Indonesia, has a dynamic and competitive market. Rotiboy, one of the well-known bread brands in Indonesia, also operates in this city, according to data obtained from the Top Brand Award (2023) bakery category. Rotiboy is ranked 3rd below Mako and Holland Bakery. Therefore, considering the intense competition, consumers must have a deep understanding of the components that influence their purchasing decisions. for the continuity of the Rotiboy business in the city of Surabaya. This research aims to examine the influence of marketing mix and social factors on purchasing decisions for Rotiboy in the city of Surabaya, mediated by purchase experience. Quantitative research method using non-probability sampling and purposive sampling technique. Data analysis techniques using Smart PLS software with hypothesis testing using PLS-based SEM. The results of the research show that the marketing mix influences purchasing decisions, purchase experience influences purchasing decisions, social factors influence purchasing decisions, social factors do not influence purchasing decisions through purchase experience and marketing mix influences purchasing decisions through purchase experience.